Download presentation

Presentation is loading. Please wait.

Published byBrian Wagner Modified over 3 years ago

1
( ) ax 2 + bx + c 2x x + 5 ac b 2(5) =10 = (2x + 1)(x + 5) check it by foiling 2x x+ 1x+ 5 2x(x + 5 ) + 1(x + 5)

2
( ) ax 2 + bx + c 3x 2 + 5x + 2 ac b 3(2) =6 =5 3 2 (3x + 2)(x + 1) check it by foiling 3x 2 + 3x+ 2x+ 2 3x(x + 1 ) + 2(x + 1)

3
( ) ax 2 + bx + c 2x x - 11 ac b 2(-11) =-22 =21 22 (2x - 1)(x + 11) check it by foiling 2x x+ -1x x(x + 11 ) + (x + 11)

4
( ) ax 2 + bx + c 8x x - 15 ac b 8(-15) =-120 = (4x + 3)(2x - 5) check it by foiling 8x x+ 6x x(2x + -5 ) + 3(2x + -5)

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google